Dampak Klinis Interaksi Obat antara Clopidogrel dan Inhibitor Pompa Proton : Tinjauan Naratif - Aslama, Ideasha; Sinuraya , Rano Kurnia; Zakiyah , Neily; Dewi , Triwedya Indra (Journal of Pharmaceutical and Sciences, 2025)
Dual antiplatelet therapy (DAPT), consisting of aspirin and P2Y12 receptor antagonists such as clopidogrel, is the mainstay treatment for patients with acute coronary syndrome (ACS). However, its widespread use can increase the risk of gastrointestinal bleeding. Proton pump inhibitors (PPIs) are often used as prophylaxis to prevent bleeding. On the other hand, PPIs are suspected of reducing the effectiveness of clopidogrel due to pharmacokinetic drug interactions. Nevertheless, findings from various studies regarding the clinical impact of this interaction remain inconsistent and controversial. The aim of this narrative review is to evaluate the effectiveness and safety of using PPIs concurrently with clopidogrel. The method used was a literature review of international journal articles discussing the interaction between PPIs and clopidogrel. The review findings indicate that certain PPIs, such as omeprazole, can inhibit the CYP2C19 enzyme involved in clopidogrel activation, potentially reducing its effectiveness. Conversely, some PPIs such as pantoprazole have minimal effects on CYP2C19 and are considered safer for concomitant use with clopidogrel. Overall, the use of PPIs can reduce the risk of gastrointestinal bleeding; however, the selection of PPI type must be carefully considered to minimize drug interactions that may compromise clopidogrel’s efficacy.